Relationsip between PTEN and VEGF Expression and Clinicopathological Characteristics in HCC - 米登海 易继林 刘恩宇 李兴睿 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
To investigate the expressions and significance of the tumor suppressor gene phosphatase and tensin homlog deleted on chromosome ten protein （PTEN） and vascular endothelial growth factor （VEGF） in hepatocellular carcinoma （HCC）, and to analyze the relationship between their expressions and the tumor＇s invasion and their pericarcinomatous tissues, the correlation of their expressions with the tumor＇s clinicopathological characteristics and invasion potential were studied. Our study showed that the expression level of PTEN in HCC was remarkably lower than that in pericarcinomatous liver tissues, while the expressions of both VEGF and MVD were higher than that in pericarcinomatous liver tissues. Correlation analysis revealed that the expression of PTEN was negatively related to the progression of the pathological differentiation and invasion of tumor, whereas the expressions of VEGF and MVD were positively related. Moreover, there was a negative relationship between the expression of PTEN and the expressions of VEGF and MVD, and a positive one between VEGF and MVD. The expressions of PTEN and VEGF may reveal the degree of differentiation and the invasive potential of HCC tissues. The mechanism by which the lack of PTEN expression probably induces abnormal hyperexpression of VEGF may play an important role in the invasion and metastasis of HCC.